Design and development of a self-nanoemulsifying drug delivery system for telmisartan for oral drug delivery - Patel, Jaydeep; Kevin, Garala; Patel, Anjali; Raval, Mihir; Sheth, Navin (International Journal of Pharmaceutical Investigation)
Background and Aim: Telmisartan (TEL) is an angiotensin II receptor blocker (ARB) antihypertensive agent. The aim of the present investigation was to develop a self-nanoemulsifying drug delivery system (SNEDDS) to enhance the oral bioavailability of poorly water soluble TEL. Materials and Methods: The solubility of TEL in various oils was determined to identify the oil phase of a SNEDDS. Various surfactants and co-surfactants were screened for their ability to emulsify the selected oil. Pseudoternary phase diagrams were constructed to identify the efficient self-emulsifying region. A SNEDDS was further evaluated for its percentage transmittance, emulsification time, drug content, phase separation, dilution, droplet size, zeta potential, pH, refractive index, and viscosity. Results: The developed SNEDDS formulation contained TEL (20mg), Tween® 20 (43.33%w/w), Carbitol® (21.67%w/w), and Acrysol® EL 135 (32%w/w). The optimized formulation of the TEL-loaded SNEDDS exhibited a complete in vitro drug release in 15min as compared with the plain drug, which had a limited dissolution rate. It was also compared with the pure drug suspension by oral administration in male Wister rats. The in vivo study exhibited a 7.5-fold increase in the oral bioavailability of TEL from the SNEDDS compared with the pure drug suspension. Conclusions: These results suggest the potential use of the SNEDDS to improve the dissolution and oral bioavailability of poorly water soluble TEL.
Keywords: Bioavailability; poor water solubility; self-nanoemulsifying drug delivery system; telmisartan